Predictors of futile recanalization after endovascular treatment in acute ischemic stroke: a multi-center study - Sun, Yu; Jou, Eric; Nguyen, Thanh N.; Mofatteh, Mohammad; Liang, Qingjia; Abdalkader, Mohamad; Yan, Zile; Feng, Mingzhu; Li, Xinyuan; Li, Guilan; Luo, Lanzhu; Lai, Yuzheng; et al. (Frontiers in Neuroscience, 2023)
Background and Objectives: Endovascular thrombectomy (EVT) improves long-term outcomes and decreases mortality in ischemic stroke patients. However, a significant proportion of patients do not benefit from EVT recanalization, a phenomenon known as futile recanalization or reperfusion without functional independence (RFI). In this study, we aim to identify the major stroke risk factors and patient characteristics associated with RFI. Methods: This is a retrospective cohort study of 297 consecutive patients with ischemic stroke who received EVT at three academic stroke centers in China from March 2019 to March 2022. Patient age, sex, modified Rankin Scale (mRS), National Institute of Health Stroke Scale (NIHSS), Alberta stroke program early CT score (ASPECTS), time to treatment, risk factors and comorbidities associated with cerebrovascular diseases were collected, and potential associations with futile recanalization were assessed. RFI was successful reperfusion defined as modified thrombolysis in cerebral infarction (mTICI) ≥ 2b without functional independence at 90 days (mRS ≥ 3). Results: Of the 297 initial patients assessed, 231 were included in the final analyses after the application of the inclusion and exclusion criteria. Patients were divided by those who had RFI (n = 124) versus no RFI (n = 107). Older age (OR 1.041, 95% CI 1.004 to 1.073; P = 0.010), chronic kidney disease (OR 4.399, 0.904 - 21.412; P = 0.067), and higher 24-hour NIHSS (OR 1.284, 1.201 - 1.373; P < 0.001) were independent predictors of RFI. Conversely, an mTICI score of 3 was associated with a reduced likelihood of RFI (OR 0.402, 0.178 - 0.909; P = 0.029). Conclusions: In conclusion, increased age, higher 24-hour NIHSS and lack of an mTICI score of 3 were independently associated with RFI and have potential prognostic values in predicting patients that are less likely to respond to EVT recanalization therapy.